Clinical Presentation of Infective Endocarditis - Rehman, Sher; Shabbier, Ghulam; Shahid, Muhammad; Shahid, Muhammad (Journal of Postgraduate Medical Institute, 2011)
In order to determine demorgraphic characteristics, various modes of presentations and distribution of clinical findings, frequencies of different valves involved, special risk factors and complications of infective endocarditis in our population, this study was conducted between September 2000 and July 2001 in the department of Medicine KTH Peshawar all patients having clinical suspicion of infective endocarditis were admitted and worked up. Out of seventy patients screened, thirty were selected fulfilling one of Duke criteria for clinical diagnosis of definite infective endocarditis. Thirty admitted patients having definite infective endocarditis. Thirty criteria were included. There were 21(70%) males and 9(30%) females. Mean age of the patients was 24 years. Ninety percent of the patients were below 40 years of age. The commonest symptoms observed were fever, shortness of breath, arthralgia/myalgia, chills, anorexia, and malaise. The most common signs were fever, cardiac murmur, anemia and splenomegaly. High ESR, anemia and RA factor positiveity topped the list of investiations.